“Let Your Stress Go and Be the Winner!” Pelatihan Manajemen Stres Bagi Siswa dalam Menhadapi Ujian - Erna Risnawati; Ratri Kartiningtyas; Fatma Nur Aqmarina (Jurnal Abdi Masyarakat (JAM), 2023)
Adolescence is a time when individuals develop their ideal self that they will achieve in the future. A teenager begins to think abstractly and has various hopes in the future or achieves goals. In an effort to achieve this dream, teenagers are required to take various school exams such as the UN, SBMPTN, UTBK, etc. Unfortunately, teenagers often feel pressured and stressed when facing these various tests which have an impact on psychological health. Often we find teenagers who have "lost" mentally before facing the real school exam. This happens because of unstable emotional conditions in adolescence, low ability to regulate emotions, lack of support from the environment to support adolescents not only in cognitive aspects but also in emotional aspects. When teenagers are able to regulate emotions by doing a good stress management, it will increasingly support teenagers in reaching their goals and future with more focus and calm in facing exams.